Political Economic Analysis of Jusyan 92.7 Fm Radio Media to Maintain Existence in the Digital Era - Ira Fakhira Ramadina; Abdul Fadli Kalaloi (Budapest International Research and Critics University, 2022)
This study aims to determine the media’s political economy by paying attention to the commodification and spatialization of Radio Jusyan 92.7 FM to maintain its existence in the digital era and the current media industry. This study uses a critical paradigm with qualitative-descriptive research methods with data collection techniques using in-depth interviews and participatory observations documented during the research. The results showed that Radio Jusyan 92.7 FM has been able to design media political economy strategies through commodification with the commodification of content, the commodification of audiences, commodification of workers, and spatialization with aspects of vertical and horizontal integration. Radio Jusyan can adapt every content it produces to the listeners’ needs and keep pace with market tastes that continue to change along with the times. In addition, Radio Jusyan provides live streaming facilities and social media platforms. Listeners who remain loyal to Jusyan’s radio broadcasts make this a selling point that can be offered to advertisers. Radio Jusyan workers are also responsible for carrying out their duties and obligations. Radio Jusyan 92.7 FM expands the same and different business fields, which is what makes Radio Jusyan able to maintain its existence to this day.